Long-term characteristics of exudative age-related macular degeneration in Japanese patients. - Masaaki Saito; Tomohiro Iida; Kuniharu Saito; Mariko Kano; Kanako Itagaki; Ichiro Maruko; Tetsuju Sekiryu (PLoS ONE, 2021)
Purpose The present study aimed to evaluate the clinical characteristics of exudative age-related macular degeneration (AMD) in Japanese patients over a 10-year period and to compare the past our report. Methods We retrospectively reviewed 1,600 treatment-naïve patients (1,777 eyes) with exudative AMD. The 10 years were divided into 2-year phases I to V. Results Of the 1,600 patients, 720 (45.0%), 733 (45.8%), 98 (6.1%), and 49 (3.1%) were diagnosed with typical AMD, polypoidal choroidal vasculopathy (PCV), retinal angiomatous proliferation, and combined subtypes, respectively. The prevalence of PCV decreased from 54.7% in phase I to 46.0% at phase V. Of the 1,777 eyes, the mean baseline logarithm of the minimum angle of resolution best-corrected visual acuities (BCVAs) in phases I, II, III, IV, and V were 0.70, 0.66, 0.55, 0.50, and 0.48, respectively. Phases III, IV, and V had significantly (P = 0.0012, P<0.0001, P<0.0001, respectively) better baseline VAs compared with phase I. The mean lesion sizes in phases I, II, III, IV, and V were 8.6, 6.7, 5.3, 5.7, and 5.7 Macular Photocoagulation Study disc areas, respectively. The sizes were significantly (P<0.0001 for all comparisons) smaller in phases III, IV, and V compared with phase I. Conclusions Although the prevalence of PCV decreased from 54.7% in phase I to 46.0% at phase V, PCV has nevertheless been highly prevalent in Japanese patients with AMD compared with Caucasian patients. The annual better baseline VAs and smaller lesion sizes over time might be related to development of treatment and better concerns about AMD.